Development of Android-Based Interactive Multimedia for Learning Topeng Tunggal Betawi Dance for Students of Dance Education Study Program, Jakarta State University - Irsyad Naufal Harits; Dwi Kusumawardani; Dinny Devi Triana (Jurnal Seni Tari, 2023)
The research aims to develop learning materials for Topeng Tunggal dance in Betawi Dance course, using interactive multimedia to optimize students' knowledge and skills. This type of research is R&D (Research and Development), using the ADDIE development procedure. The research subjects were students of class 2021. Research data collected by observation, interviews analyzed qualitatively and questionnaires quantitatively. The results of the expert test stage obtained an average score from material experts of 3.53, meaning "Very Good", with improvements: 1) costume name, 2) instrument design, and 3) instrument name. Learning experts 3.706 means "Very Good", with improvements: 1) evaluation features, 2) error buttons, 3) mask design, and 4) writing techniques. Media expert 3.075 means "Very Good", with improvements: 1) completeness of explanatory text, 2) consistency of navigation, 3) image size, 4) consistency of visual style, and 5) completeness of original photos of various dance motifs. The trial phase was carried out on 12 students in a small group, the results were in the form of comments including: 1) the media is interesting, 2) varied, 3) suitable for independent learning, 4) useful to help understanding and skills, 5) the application is not boring, and 6) the application is uniquely different from the others. The conclusion of the research is that D-Moleap interactive multimedia is very feasible to use, because it has features that are very helpful in practical learning and has fulfilled the criteria as a good interactive multimedia.